Acculturational Homophily in Friendships based on English-Name Usage: A Natural Experiment - Dafeng Xu (European Regional Science Association (ERSA), 2015)
This paper examines acculturational homophily in friendships of international students. Acculturation (also known as cultural assimilation) is measured by English-name usage. I use data from Renren.com, a Facebook-type social networking site based in China. The sample consists of students who have bachelor's degrees in China and have or will have graduate degrees in the U.S. On Renren, students have the option to add English names after their Chinese names, which quantifies acculturational characteristics. The difficulty of pronouncing the original Chinese name by native speakers of English creates a natural experiment on English-name usage. Using OLS and IV models, I find that a student who shows the English name online has more close friends who also show English names online. This provides empirical evidence that individual immigrants tend to have friends with similar acculturational characteristics.
Keywords: J1; R2; Z1; 330; acculturation; homophily; English name; friendship; immigration